Optimalisasi Kapasitas Elite Governing dan Non-Governing Nagari Tuo Pariangan pada Pelaksanaan Pacu Jawi - Aulia, Fachri Rahmad; Arifin, Zainal; Putri, Indah Adi (Nakhoda: Jurnal Ilmu Pemerintahan, 2024)
The success of the nagari government program is determined by the capacity of the leadership elements. This research aims to analyze the capacity of the governing and non-governing elite of Nagari Tuo Pariangan in implementing pacu jawi. This research uses UNDP institutional capacity theory and JICA individual capacity. The method used is a qualitative instrumental case study approach. The results of this research are that the capacity of the governing elite of Nagari Tuo Pariangan has not been maximized in using human resources, capital and policy direction. The governing elite does not accommodate resources for the creation of trading facilities in the jawi racetrack. The capacity of the non-governing elite of Nagari Tuo Pariangan has also not played an effective role in organizing the pacu jawi. This is because bundo kanduang and religious scholars do not play an optimal role in carrying out the pacu jawi event. Several recommendations to increase the capacity of the governing elite of Nagari Tuo Pariangan, namely using a mixed top down & bottom up policy, giving tasks to bureaucrats to search for the location of the pacu jawi rice fields, allocating village funds for pacu jawi activities, creating materials and designing attractive funding proposals, preparing materials creation of traders’ stalls, using the concept of community based tourism (CBT) involving traditional elements, pacu jawi fans, people who own rice fields, people who are involved in agricultural businesses. Next, on the evaluation agenda, the Nagari Tuo Pariangan Government must interact with all actors in the pacu jawi event and accommodate suggestions submitted by each actor. Several recommendations to increase the capacity of the non-governing elite of Nagari Tuo Pariangan, such as providing renewal, adding traditional and cultural nuances, holding Nagari Tuo Pariangan cultural arts at the jawi runway, proposing a typical nagari culinary bazaar and holding an exhibition of Nagari Tuo Pariangan tambo literary works.